Hubungan Status Gizi dan Ansietas Terhadap Hipertensi Pada Lansia Di Puskesmas Pakjo Kota Palembang Tahun 2023 - Abu Bakar Sidik; Sasono Mardiono (Madani: Jurnal Ilmiah Multidisiplin, 2023)
One of the most common degenerative diseases is hypertension. Hypertension can be caused by problems with excessive nutritional status in the elderly and can also be caused by excessive anxiety experienced by the elderly. This problem of excessive nutritional status and excessive anxiety triggers the emergence of the degenerative disease hypertension. This study aims to determine the relationship between nutritional status and anxiety on hypertension in the elderly. This type of research is quantitative using a cross sectional approach. This research was conducted from 19 May 2023 to 5 June 2023 at the Pakjo Health Center, Palembang City. The sample for this study was elderly people with hypertension who visited the 23 Ilir Palembang Community Health Center in 2023, totaling 55 elderly people. The results of this study show that there is a relationship between nutritional status and the level of hypertension in the elderly (p=0.001) and a relationship between the level of anxiety and hypertension in the elderly (p=0.033). It is hoped that the 23 Ilir Palembang Community Health Center will be able to increase community health efforts with elderly posyandu activities and other supporting programs such as elderly exercise and pro-elderly activities.